Optimization of light collection from crystal scintillators for cryogenic experiments - Danevich, F; Kobychev, R; Kobychev, V; Kraus, H; Mikhailik, V; Mokina, V (2014)
High light collection efficiency is an important requirement in any application of scintillation detectors. The purpose of this study is to investigate the possibility for improving this parameter in cryogenic scintillation bolometers, which can be considered as promising detectors in experiments investigating neutrinoless double beta decay and dark matter. Energy resolutions and relative pulse amplitudes of scintillation detectors using ZnWO4 scintillation crystals of different shapes (cylinder â̂... 20×20 mm and hexagonal prism with diagonal 20 mm and height 20 mm), reflector materials and shapes, optical contact and surface properties (polished and diffused) were measured at room temperature. Propagation of optical photons in these experimental conditions was simulated using Geant4 and ZEMAX codes. The results of the simulations are found to be in good agreement with each other and with direct measurements of the crystals. This could be applied to optimize the geometry of scintillation detectors used in the cryogenic experiments. © 2014 Elsevier B.V.